إستراتجية الذكاء الإقتصادي لاستدامة المقاولاتية مع الإشارة لحالة الجزائر - كیموش بلال (Finance and Business Economies Review, 2017)
As a result of developments and changes rapidly and the increasing emergence of new technologies in the economic environment that has led to the intensification of competition between economic institutions since the imposition of the vigilance and the exploitation of strategic information to ensure the survival and adapt to the activity environment, which prompted the need to work to embody the requirements for ensuring the success and sustainability, especially entrepreneurial including It contributes to the acquisition of value and competitive advantage that ensures whereby continuity and development in the field of activity, and here highlights the role of the so-called economic intelligence that contributes to building its strategy as one of the supporting elements for the success of entrepreneurship in the future. In Algeria, for the promotion of economic institutions and rehabilitation and to achieve sustainability, including entrepreneurial found sought to help them cope with the economic intelligence requirements, knowing that the intelligence economic and entrepreneurial in Algeria are still boys and from this paper came to know the extent of the contribution of economic intelligence in the continuity of entrepreneurial activity in Algeria review and reality each of them and try to highlight the importance of the adoption of this type of organization on economic intelligence in Algeria to allow continuity and face competition with other institutions, whether local or foreign ones.